The Role of Realistic Mathematics Education in Developing Critical Thinking Skills: A Systematic Literature Review - Hanipa Hanipa; Duano Sapta Nusantara; Rohati Rohati (Journal of Instructional Mathematics, 2026)
Although critical thinking is fundamental to 21st-century mathematics learning, research synthesizing how Realistic Mathematics Education (RME) develops this competency remains fragmented and underexplored. This study aims to map the literature profile, development trends, as well as challenges and recommendations of research related to the integration of RME and critical thinking abilities. A Systematic Literature Review (SLR) method was applied to 18 articles from Scopus and Google Scholar for the period 2019-2025 using VOSViewer bibliometric analysis. The results show that RME consistently improves critical thinking abilities through three clusters: learning implementation, RME characteristics based on real contexts, and effectiveness evaluation. Research trends evolved from effectiveness verification (2019-2021), technology integration (2022-2023), toward differentiated learning and exploration of local cultural contexts (2024-2025). This evolutionary pattern raises a critical question: whether such trends reflect the theoretical maturity of RME as a robust and coherent pedagogical framework, or whether they indicate fragmentation of approaches that risks diluting the core principles of RME. Main challenges include variations in learning design quality and limited digital infrastructure. The study recommends continuous RME implementation, strengthening of teacher education curriculum, and development of specific critical thinking measurement instruments for RME based mathematics learning are needed.